A Comparative Analysis between DCT and JPEG2000 Modules Algorithms - Hassan M. Ibrahim; Mohammed Sh. Majid; Ali N. Yousif (Zien Journals, 2022)
Analysis and comparison Discrete Cosine Transform (DCT), and JPEG2000. Both modules were experimented in a bitmap figure in a software called VCDemo, with changing the properties of each module for every experiment. This paper focuses on noting down the comparative analysis with JPEG2000 and DCT. As well as, to make a brief literature review of the latest research works on JPEG2000 and DCT worldwide.
Keywords: JPEG2000; DCT; VCDemo; Encoder